Perspective Armour-Piercing Intermediate Cartridge Projectile - Krzysztof PIASTA (Perspektywiczny przeciwpancerny pocisk naboju pośredniego, 2023)
Ongoing military conflicts, along with a constant evolution of individual protection devices, have shown an urgent need of development in terms of the armour piercing capability of standard infantry small arms ammunition. The following paper includes a brief overview of the existing armour-piercing intermediate rounds, in an effort to define the most reasonable design of a perspective armour-piercing projectile. Therefore, various projectiles were designed and evaluated in terms of their external ballistic performance for chosen initial conditions, followed by preliminary internal and terminal ballistic calculations that were performed in order to assess the most reasonable outcome.
Keywords: Amunicja strzelecka